The Effect of the Flipped Classroom Model with the STEAM Approach on Students' Spatial Abilities in Learning Geography - Muhammad Isna Qurrata Ayun; Chul-ki Cho; Thabile Zondi (Journal of Social Knowledge Education (JSKE), 2023)
Purpose of the study: The purpose of this study was to determine the effect of the spatial abilities of students using the Flipped Classroom model with the Science, Technology, Engineering, Art and Mathematics learning approach using the expository model in class X IPS SMA N 1 Kartasura in the 2020/2021 academic year. Methodology: The method used is quasi-experimental with the Post Test Only Control Group Design research design. The population in this study were all class X IPS students at SMA N 1 Kartasura. Data collection techniques are carried out by observation, testing and documentation. The analysis test technique uses one-way Anava with a test with a level of 5%. Main Findings: Based on the results of the analysis, it was concluded that there was a significant influence on the spatial abilities of students who used the Flipped Classroom model with the Science, Technology, Engineering, Art and Mathematics learning approach with the expository model in class X IPS SMA N 1 Kartasura in the 2020 academic year. Novelty/Originality of this study: The novelty of this study can be seen from its aim to determine the effect of the spatial abilities of students who use the Flipped Classroom model with the Science, Technology, Engineering, Art and Mathematics learning approach with the expository model in class X IPS SMA N 1 Kartasura in the 2020/2021 academic year. The limitation of this study is that it only measures the effect of the flipped classroom model using the STEAM approach.